Geo-Congress 2022 Site and Soil Characterization, Computational Geotechnics, Risk, and Lessons Learned. - Lemnitzer, Anne (American Society of Civil Engineers, 2022)
GSP 333 contains 71 peer-reviewed papers on site and soil characterization, computational geotechnics, and risk presented at Geo-Congress 2022, held in Charlotte, North Carolina, March 20-23, 2022.
Description based upon print version of record.
Keywords: Geotechnical engineering -- Data processing -- Congresses.; Geotechnical engineering -- Risk assessment -- Congresses.; Soil mechanics -- Congresses.; elektronické knihy; electronic books